Long-run supply prospects - W. Robertson (Intereconomics, 1969)
In spite of the growth of population and the inevitable push towards better living conditions which must involve a growing demand for industrial materials, there seems little justification for fears of scarcities of materials, apart of course from the temporary scarcities and temporary high prices which are due to fluctuations in supply and demand. These temporary scarcities are particularly likely in primary producing industries such as the copper industry, where a miscalculation of demand leads to a temporary shortage because of the long gestation period of investment. But this is a very different situation from the long-run scarcities which are sometimes portrayed. It is worth emphasising this since mistaken ideas about the future scarcity of natural materials can damage the developing countries which are heavily dependent on natural materials. They are made to believe that the long-term supply prospects for natural materials are poor, and that therefore there must be an overhasty development of synthetic materials. While we would certainly not deny the value of these materials for both developed and developing countries, it is a question of the best allocation of resources between developing supplies of natural materials and those of synthetic materials.
Keywords: 330; Raw Materials